Smart Governance in Health: Linking Strategic Human Resource Management, Technology Integration, and Public Health Performance in Central Java (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This study explores the interconnection between Strategic Human Resource Management (SHRM), technology integration, and public health performance within the framework of smart governance at the Provincial Health Office of Central Java, Indonesia. Using a qualitative method with a strategic approach, this research aims to identify how strategic alignment between human resource capabilities and technological advancement contributes to the enhancement of health service delivery in the public sector. Data were collected through in-depth interviews with key stakeholders, including policymakers, HR managers, IT personnel, and public health experts, supported by document analysis and field observation.Findings reveal that the implementation of SHRM practicessuch as strategic talent development, performance-based systems, and leadership empowermentplays a critical role in enabling the adoption of digital health technologies. Moreover, technology integration is not merely a technical adaptation but requires organizational readiness, digital culture, and continuous policy innovation. The synergy between SHRM and technology contributes to improved public health outcomes, faster response to health crises, and better data-driven decision-making. However, institutional barriers, fragmented coordination, and limited digital infrastructure remain significant challenges.This study offers strategic insights for provincial health governance, emphasizing the importance of long-term planning, interdepartmental collaboration, and capacity building. It recommends developing an integrated smart health governance roadmap that aligns HR policies with technological innovations to support sustainable public health performance. The findings contribute to the growing discourse on digital transformation in the health sector, particularly within emerging economies facing complex governance structures.